Social innovation and the promotion of local economic development - Ana Clara Aparecida Alves de Souza; Bruno de Souza Lessa; José Carlos Lázaro da Silva Filho (Innovation & Management Review, 2019)
Purpose: The purpose of this study is to propose a multidimensional view of social innovation. Design/methodology/approach: It offers a detailed analysis of the activities performed by ADEL (Agência de Desenvolvimento Econômico Local) - a regional non-governmental organization located in one of the poorest regions of Brazil - which is succeeding in engaging young people in the promotion of local development. The case was analysed drawing on the dimensions structured by researchers of one of the main centres of social innovation in the world, the Centre de Recherche sur Les Innovations Sociales (CRISES) based in Canada. Findings: The results found characterize ADEL as a social innovation based on the dimensions of social innovation described in the CRISES' conceptual encyclopaedia (Tardif and Harrison, 2005). The results highlight the singularities of the case studied, which allowed the elaboration of a revisited table of dimensions proposed by the CRISES' researchers. Research limitations/implications: For future studies, using the CRISES' table as reference of analysis for other social innovations, the possibility suggested is the quantitative exploration of these dimensions. Originality/value: the originality of this article lies in the fact that it presents a representative social innovation for the Brazilian semiarid.
Keywords: 650; Local development; Dimensions; Social innovation